2013
DOI: 10.1007/s13187-013-0452-6
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship Clinic Group Educational Sessions: Adoption, Acceptance, and Attendance

Abstract: The number of breast cancer survivors now exceeds 2.5 million in the USA. In the near future, it is likely that existing systems will not be sufficient to provide follow-up care and services for all these patients. Because survivors have many concerns in common and providers may not have enough time to address them individually, group educational sessions (GES) provide an opportunity to inform patients of current breast cancer-related health issues, treatment updates, and follow-up guidelines in an efficient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Two patients mentioned at clinic visits that they had not made an OT appointment due to scheduling conflicts with work. Other studies examining non-attendance at medical appointments/programs have also found health problems [15,23], language [15], and work [15,23,24] as barriers to attendance. For example, Wheelock and colleagues [15] reported that 14 patients declined an invite to an educational session due to a medical condition or their elderly status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two patients mentioned at clinic visits that they had not made an OT appointment due to scheduling conflicts with work. Other studies examining non-attendance at medical appointments/programs have also found health problems [15,23], language [15], and work [15,23,24] as barriers to attendance. For example, Wheelock and colleagues [15] reported that 14 patients declined an invite to an educational session due to a medical condition or their elderly status.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies examining non-attendance at medical appointments/programs have also found health problems [15,23], language [15], and work [15,23,24] as barriers to attendance. For example, Wheelock and colleagues [15] reported that 14 patients declined an invite to an educational session due to a medical condition or their elderly status. In contrast to our study, previous studies also reported forgetfulness [23][24][25], transportation [24], and lack of interest [15] as barriers to attendance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brothers, Easley, Salani, and Andersen (2013) used an oncology-led intervention, whereas Grunfeld et al (2006Grunfeld et al ( , 2011 and Wattchow et al (2006) used a primary care provider-led model. Two studies focused on a nurse-led model of survivorship care (Curcio, Lambe, Schneider, & Khan, 2012;Jefford et al, 2011), and one study used a specialized survivorship clinic as the model for their intervention (Wheelock et al, 2013).…”
Section: The Interventionmentioning
confidence: 99%